VIRTUAL INFLUENCERS AND DIGITAL ENGAGEMENT: KEY INSIGHTS FROM INDONESIA'S YOUNGER CONSUMERS - Agung Stefanus Kembau; Arifmanuel Kolondam; Nancy Henrietta Jessamine Mandey (Jurnal Manajemen Pemasaran, 2024)
This study addresses a critical gap in digital marketing by examining the impact of virtual influencers on consumer engagement, focusing on Gen Z and Gen Y in Indonesia’s Jabodetabek region. While virtual influencers are gaining traction globally and locally, limited research has explored the factors that drive consumer interaction in diverse, digitally evolving markets like Indonesia. This study investigates the roles of perceived authenticity, content quality, and technological sophistication, with a particular emphasis on the moderating effect of digital literacy—a factor often overlooked in previous research. Data from 179 respondents were analyzed using Structural Equation Modeling (SEM) with SmartPLS. The findings reveal that perceived authenticity, content quality, and technological sophistication significantly enhance consumer engagement with virtual influencers, especially among digitally literate consumers. Digital literacy plays a critical moderating role, amplifying the impact of these influencer attributes and highlighting the importance of digital fluency in consumer interactions with advanced digital personas. These insights offer a theoretical contribution to the literature on influencer marketing and provide practical guidance for Indonesian brands seeking to connect with younger, tech-savvy audiences. By prioritizing authenticity, high-quality content, and appropriate technological sophistication, brands can strategically leverage virtual influencers to cultivate deeper, more meaningful engagement in Indonesia’s rapidly evolving digital landscape.